通識課程專業化芻議： 以問題意識和課程品質為取徑 A Brief Discussion of Professionalizing General Education: Approaching by Problem Awareness and Curriculum Quality - 陳淑敏 Amy Shumin Chen; 劉柏宏 Po-Hung Liu; 劉美慧 Mei-Hui Liu (Journal of Curriculum Studies)
隨著政治民主和社會脈絡的變遷，臺灣的通識教育逐步發展和演變。從1958年教育部所頒布「共同必修科目」，直至1994年透過大法官會議解釋條文廢除相關規定，通識教育也經歷自由化與自主化的洗禮。然而，長期以來臺灣高等教育片面重視專業教育的效益，導致通識課程處於邊緣化或破碎化的危機。因此，建構通識教育的專業化具有重要性。本文以通識教育專業化的課程實踐案例，凸顯建構問題意識和深化課程品質的取徑，期能對於提升通識教育的課程品質及學術承載度發揮引導作用。讓臺灣的通識教育之發展與優化，能更有效回應大學校院培育人才的教育目標。 General education has gradually evolved and changed alongside the developing political democracy and social contexts in Taiwan. Beginning with the issuance of the “Common Required Subjects” by the Ministry of Education in 1958 and continuing until the abolition of the relevant regulations by the Judicial Yuan’s interpretation in 1994, general education underwent a process of liberalization and increased autonomy. However, for a long time, the higher education system in Taiwan placed excessive emphasis on the benefits of professional education, leading to the marginalization or fragmentation of general education courses. Therefore, the professionalization of general education has become critically important. This paper analyzes the curriculum practices related to the professionalization of general education to highlight approaches for fostering problem awareness and enhancing curriculum quality, which serve as guiding principles for improving the quality and academic rigor of general education. By developing and optimizing Taiwan’s general education, universities can more effectively meet their educational goals of cultivating talent.